化简 a^m+1*a^3-2a^m*a^4-3a^2*a^m+2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 13:38:47
化简a^m+1*a^3-2a^m*a^4-3a^2*a^m+2化简a^m+1*a^3-2a^m*a^4-3a^2*a^m+2化简a^m+1*a^3-2a^m*a^4-3a^2*a^m+2原式=a^(m
化简 a^m+1*a^3-2a^m*a^4-3a^2*a^m+2
化简 a^m+1*a^3-2a^m*a^4-3a^2*a^m+2
化简 a^m+1*a^3-2a^m*a^4-3a^2*a^m+2
原式=a^(m+1)×a³-2a^m×a^4-3a²×a^(m+2)
=a^(m+1+3)-2a^(m+4)-3a^(2+m+2)
=a^(m+4)-2a^(m+4)-3a^(m+4)
=(1-2-3)×a^(m+4)
= -4a^(m+4)
a^m-1*a³-2a^m*a^4-3a²*a^m+2
化简 a^m+1*a^3-2a^m*a^4-3a^2*a^m+2
(-a)^2m+1÷a^m
已知a^3*a^m*a^2m+1=a^25,求m的值
2a^(2m+3)(-a)^2/(-a)^(m-1)=-2(a^3)^(m-1)/a m为多少
因式分解:(-a)^m+a*(-a)^m-1
a^m+1×a^3-2a^m×a^4-3a^2×a^m+2,第一采用!
a的m次方×a的3m次方×a×a的m次方-2a的3m次方×a的2m次方+1等于几
a^m·a^3m·a·a^m-2a^3m·a^2m+1 计算
(a-b)^m+3(b-a)^2(a-b)^m
化简(a^2-a+1)^m(a-a^2-1)^2n(a-a^2-1)
-12a^2m-1b^m+1+20a^m-1b^2m+3
a^m-1+a^m-a^m+1 因式分解
已知:a^m=2 a^n=3 求a^m+1 a^n+3 a^m+n a^m+n+2
A(m,
[(-a)^2m]^3*a^3m+[(-a)^3m)]^3,(m为偶数),计算.
2a^(m+1)+4a^(m)-2a^(m-1) m为正整数
分解因式 a^m-a^(m+1)